Changes in Growth and Biochemical Parameters of Groundnut (Arachis hypogaea L.) Influenced by TANFAC Effluent - D. Arulbalachandran, S. Dhanam (Journal of Phytology, 2009)
Wastewater discharged by the industries is one of the major causes of environmental pollution, particularly in the developing countries. Present study was conducted in influence of TANFAC effluent (0, 10, 25, 50, 75 and 100%) on groundnut varieties (Arachis hypogaea L.) var. TMV-7, TMV-2, TMV-10 and TMV-13). The growth parameters such as seedling vigour, vigour index, tolerance index and percentage of phytotoxicity were measured on 10th day seedlings. The morphological and biochemical parameters such as chlorophyll, carotenoid, sugar and starch contents decreased with the increase of effluent concentrations except 10% effluent concentration. Among the four varieties studies TMV-7 performed better under TANFAC factory effluent treatment and it proved to be tolerant when compared to the remaining varieties.